Combination of Adoptive Cell Therapy and Radiotherapy in Cancer Management - Vito Filbert Jayalie; Endang Nuryadi (Radioterapi & Onkologi Indonesia, 2022)
Cancer remains a healthcare burden in the world, with the increasing cases and deaths. Adoptive cell therapy (ACT) is one of the immunotherapies which modifies immune system to recognize cancer cells, which is then transfused to induce antitumoral responses in the human body. ACT works by using cancer-specific immune cells, especially Natural Killer and T cells in the form of tumor-infiltrating lymphocytes, T-cell receptor or chimeric antigen receptor. As the combination therapy with radiotherapy, radiation is able to induce tumor-associated antigen (TAA) and major histocompatibility complex (MHC) class I expression, which leads to increased immune cells around the tumor. As the result, transferred ACT to the body may be able to proliferate and perform its function well. Moreover, radiotherapy is able to downregulate regulatory T cells and myeloid-derived suppressor cells which can inhibit the role of the immune system in attacking cancer. Clinically, studies combining radiation and ACT in cancer care are limited to several types of cancer, such as metastatic melanoma, nasopharyngeal cancer, lymphoma and non-small cell lung cancer. Radiotherapy is able to increase therapeutic efficacy, especially as a bridging therapy before ACT. Nevertheless, further trials to know the potency of combining ACT and radiotherapy in other types of cancer, especially in earlier stages are needed.